Produção sustentável de leite bovino em área de proteção ambiental: aplicação da análise energética no município de Torre de Pedra/SP - Silva, Marísia Cristina da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Agricultural activity is considered one of main sources of food supply for humanity. It contributes to local, regional, and national development. However, the activity results in significant adverse environmental impacts when it is not developed based on social, economical and environmental sustainability aspects. The need of an efficient use of natural resources with a minimal environmental impact poses as a challenge when it is related to the solution of problems resulted from the use of energy sources coming from the environment. The establishment of organized productive systems for local farmers provides better management of local natural resources besides favoring, from a sustainability perspective, a better economic organization of the environment. The town of Torre de Pedra / SP is part of the Environmental Protection Area Corumbataí-Botucatu-Tejupa, Perimeter Botucatu The region has a traditional vocation for dairy farm production and it presents problems ranging from environmental to socioeconomic aspects. This project focus on the identification and analysis, with regards to energy, of bovine milk production systems in family farms located in Torre de Pedra/SP. There were performed technical visits to the farms in order to gather quantitative and qualitative data. The farmers were asked to respond to semi-structured questionnaires in order to help us to establish detailed conditions for the analysis of production systems to be studied. Thus, potential drawbacks related to the external dependence on non-renewable energy sources were identified based on the years 2011 and 2012. The direct energy, coming from biological and fossil fuel sources, and indirect energy coming from industrial sources, were measured based on the data collection as well as the energetic outflows of two 4 ...

A atividade agropecuária é uma das principais fontes de fornecimento de alimentos para a humanidade além de contribuir para o desenvolvimento local, regional, e nacional. Porém, quando não desenvolvida em bases social, econômica e ambientalmente sustentáveis, acarreta significativos impactos adversos ao meio ambiente. A necessidade em utilizar de forma eficiente os recursos naturais com mínimo impacto ambiental torna-se um desafio para solucionar o problema do uso e energia oriunda do meio ambiente. A organização dos sistemas produtivos da agricultura familiar proporciona melhor gestão dos recursos naturais locais, além de favorecer uma melhor organização econômica do ambiente na perspectiva de sustentabilidade. O município de Torre de Pedra/SP, que compõe a Área de Proteção Ambiental Corumbataí-Botucatu-Tejupá, Perímetro Botucatu, de tradicional vocação na produção de leite bovino, apresenta problemas de cunho ambiental e socioeconômico. O presente trabalho teve por objetivo identificar e analisar energeticamente os sistemas de produção de leite bovino em propriedades familiares no município de Torre de Pedra/SP. Foram realizadas visitas técnicas para coleta de dados quantitativos e qualitativos, por intermédio da aplicação de questionários semiestruturados, juntamente a produtores de leite do município, capazes de estabelecer condições detalhadas de análise dos sistemas de produção a serem estudados. Assim, foram apontados possíveis gargalos quanto à dependência externa de fontes não renováveis de energia, tomando por base os anos de 2011 e 2012. Com a coleta de dados, foram avaliadas a energia direta, provinda de fontes biológicas e fósseis, e a ...
Keywords: Agricultura familiar; Bovino de leite; Sustentabilidade; Family farms